Odkrycie krajobrazu - Szeszuła, Szymon; Karatani , Kōjin (Przestrzenie Teorii, 2025)
This article reinterprets Natsume Sōseki’s Theory of Literature (Bungakuron, 1906) as a historically premature intervention that exposes the contingent, nineteenth-century construction of “literature” and “literary history.” It argues that Sōseki’s apparently eccentric question – “What is literature?” – targets the hidden historicity behind claims of Western universality and rejects linear developmental narratives and “-isms” as explanatory wholes. In place of periodizing categories, the article highlights Sōseki’s formalist impulse (including his F+f model), which treats “romanticism” and “naturalism” as variable elements within works rather than successive stages. The article further links this critique to the Meiji-era “discovery of landscape” as an epistemological shift: landscape becomes visible only through an inversion of perception associated with the “inner man.” By reading Kunikida Doppo’s Unforgettable People alongside the reclassification of sansuiga under Western pictorial frameworks, it shows how realism and interiority co-produce modern forms of representation. Ultimately, the article suggests that Sōseki’s theoretical impasse does not simply precede his fiction but helps generate it, making critical distance from “literature” the condition of his creativity.